2000
DOI: 10.1002/1098-2779(2000)6:2<148::aid-mrdd10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Williams syndrome: Cognition, personality, and adaptive behavior

Abstract: Williams syndrome is caused by a microdeletion of at least 16 genes on chromosome 7q11.23. The syndrome results in mild to moderate mental retardation or learning disability. The behavioral phenotype for Williams syndrome is characterized by a distinctive cognitive profile and an unusual personality profile. Relative to overall level of intellectual ability, individuals with Williams syndrome typically show a clear strength in auditory rote memory, a strength in language, and an extreme weakness in visuospatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
119
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(128 citation statements)
references
References 37 publications
2
119
1
3
Order By: Relevance
“…This neuropsychological profile with relatively intact language and, concerning adaptive behavior, strength in communication is in line with that observed in typically deleted WBS individuals. [15][16][17] Careful analysis of facial features of patients with atypical deletion and varying degrees of craniofacial abnormalities and animal model studies suggest that genes at both proximal and distal ends of the deletion are involved in WBS craniofacial features. 3,[18][19][20][21] In particular, two genes have been postulated to be mainly involved in the craniofacial features of WBS, GTF2IRD1, and BAZ1B.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…This neuropsychological profile with relatively intact language and, concerning adaptive behavior, strength in communication is in line with that observed in typically deleted WBS individuals. [15][16][17] Careful analysis of facial features of patients with atypical deletion and varying degrees of craniofacial abnormalities and animal model studies suggest that genes at both proximal and distal ends of the deletion are involved in WBS craniofacial features. 3,[18][19][20][21] In particular, two genes have been postulated to be mainly involved in the craniofacial features of WBS, GTF2IRD1, and BAZ1B.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…Research has demonstrated that WS is associated with deficits in adaptive behavior [14]- [16]. Researchers found that children with WS obtained significantly lower scores in adaptive behavior compared to their IQ-and chronological age (CA) matched counterparts with nonspecific intellectual disability [17].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with WS appear RUNNING HEAD: Social Approach in Williams syndrome 4 hypersociable from an early age (Doyle, Bellugi, Korenberg & Graham, 2004), demonstrating an eagerness to make eye contact with and to approach strangers (Mervis & Klein-Tasman, 2000). An interest in looking at faces remains in childhood and into young adulthood (Riby & Hancock, 2008).…”
mentioning
confidence: 99%